Effect of Potato virus Y on the NADP-malic enzyme from Nicotiana tabacum L.: mRNA, expressed protein and activity - Doubnerová, Veronika; Müller, Karel; Cerovská, Noemi; Synková, Helena; Spoustová, Petra; Ryslavá, Helena (International journal of molecular sciences, 2009)
The effect of biotic stress induced by viral infection (Potato virus Y, strain NTN and O) on NADP-malic enzyme (EC 1.1.1.40) in tobacco plants (Nicotiana tabacum L., cv. Petit Havana, SR1) was tested at the transcriptional, translational and activity level. The increase of enzyme activity in infected leaves was correlated with the increased amount of expressed protein and with mRNA of cytosolic NADP-ME isoform. Transcription of the chloroplastic enzyme was not influenced by viral infection. The increase of the enzyme activity was also detected in stems and roots of infected plants. The effect of viral infection induced by Potato virus Y, NTN strain, causing more severe symptoms, was compared with the effect induced by milder strain PVY(O). The observed increase in NADP-malic enzyme activity in all parts of the studied plants was higher in the case of PVY(NTN) strain than in the case of strain PVY(O). The relevance of NADP-malic enzyme in plants under stress conditions was discussed.
Keywords: Nicotiana; Plant Leaves; real time-PCR; messenger RNA; Potyvirus; Plant Diseases; Potato virus Y strain O (PVYO); Malate Dehydrogenase; listy rostlin; protein - isoformy; Protein Isoforms; RNA, Messenger; malátdehydrogenasa; kořeny rostlin; tabák; nemoci rostlin; Nicotiana tabacum L.; NADP-malic enzyme; Plant Stems; Plant Roots; Potato virus Y strain NTN (PVYNTN); stonky rostlin; biotic stress